POWER IN COMMUNITY: PENGUATAN USAHA PRODUK AREN PADA MASYARAKAT LOKAL DI KAMPUNG SYUNAI DISTRIK BIKAR KABUPATEN TAMBRAUW - Maruapey, Azis; Lestaluhu, Rajab; Saeni, Fajrianto; Nanlohy, Lona H.; Hahury, Sanny; Maipauw, Niny J. (Indonesian Collaboration Journal of Community Services (ICJCS), 2025)
The aim of this service is to stimulate Power in Community to strengthen the Aren product business in the local community in Syunai Village, Bikar District, Tambrauw Regency. Actions carried out to awaken the mindset, creativity and entrepreneurial spirit of local communities through actions to strengthen the Aren product business so that it has economic value for local households. This activity was carried out collaboratively and synergistically between the local community and UM Sorong lecturers. The method used in Power in Community: Strengthening the Palm Sugar Product Business in the Local Community in Syunai Village through stimulation of strengthening the product business carried out in the form of Collaborative Action activities with a persuasive and andragogical approach model. The results of this community service activity have identified how to build understanding (mindset) and creative power of local communities in increasing the diversification of palm derivative products and opening up market information. This empowerment also becomes the main foundation for strengthening and developing the sugar palm product business as a superior regional commodity